Feasibility of an optimum currency area in ASEAN-5 countries - Chaiphat, Channarong (Kasetsart Journal of Social Sciences, 2017)
This study examined the feasibility of having an optimum currency area in the ASEAN-5 (Indonesia, Malaysia, the Philippines, Singapore, and Thailand) by studying whether the economic variables of these 5 ASEAN countries are congruent. Four ASEAN economic variables consisting of: 1) real gross domestic product, 2) consumer price index, 3) real interest rate, and 4) foreign exchange rate were analyzed using a structural vector autoregression model to identify relationships or responses of economic variables in the ASEAN-5 in the event of a shock. The findings revealed that two of the four economic variables of the ASEAN-5 respond to shocks in the same direction—that is, the real interest rate and the exchange rate will have an increasing response to the change. The real gross domestic product will also have an increasing response to the change in almost all countries except in the Philippines, while the consumer price index will respond to both appreciation and depreciation in an asymmetrical manner. This study showed that the economic variables of the ASEAN-5 meet some of the necessary criteria of the optimum currency area theory. Therefore, this study sheds some light on how to prepare for the setting up of the appropriate optimum currency area for the ASEAN-5 if monetary integration were to occur in the future. It can be concluded that monetary integration could be feasible because 2 out of the 4 fundamental economic variables are congruent. However, it will take some time to synchronize all of the variables, especially the consumer price index, which is still asymmetric at this point.